Chemiese beheer van Bromus diandrus Roth. in Triticum aestivum L. met clomazone en foraat - Barry, Renaldo Jean (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 1996.